OP0334 Efficacy and safety of continuing versus withdrawing adalimumab (ADA) in maintaining remission in patients with non-radiographic axial spondyloarthritis (NR-AXSPA). (12th June 2018) - Landewé, R.; Sieper, J.; Mease, P.; Inman, R.; Wang, X.; Li, M.; Pangan, A.; Anderson, J.
Abstract : Tapering and flaring in PsA and SpA Background: It is not known whether TNF blockers can be stopped in nr-axSpA patients (pts) who are in remission. Objectives: ABILITY-3, reported here, assessed if ADA can be discontinued or should be continued in nr-axSpA pts in sustained remission after a 28-wk open-label period. Methods: ABILITY-3 enrolled adult pts diagnosed with nr-axSpA, fulfilling ASAS criteria but NOT modified New York criteria who had objective evidence of active MRI inflammation in the SI joints or spine or elevated high-sensitivity CRP at screening, active disease at baseline (ASDAS ≥2.1, BASDAI≥4, total back pain ≥4), and inadequate response to ≥2 NSAIDs. Pts who achieved ASDAS inactive disease (ASDAS <1.3) with open-label ADA 40 mg every other wk at wk 16, 20, 24, and 28 were randomised to 40-wk, double-blind PBO (withdrawal) or ADA (continuation) in period 2. Primary efficacy endpoint was proportion of pts who did not experience a flare (ASDAS ≥2.1 at 2 consecutive study visits) during period 2. Secondary endpoints were also assessed up to wk 68 (nonresponder imputation). Results: Of 673 enrolled pts, 305 (45%) were randomised to double-blind treatment. A significantly greater proportion of pts treated with ADA vs PBO had no flares (70% vs 47%; p<0.001) at wk 68; relative risk of flare with treatment withdrawal was 1.77. Time to flare analysis showed significantly lower risk of flare for ADA vs PBO (figure 1). At wk 68, significantly greater proportions of ADA vs PBO pts achieved secondary endpoints, except for HAQ-S (table 1). Among pts who received ADA at any time, 77% reported adverse events (AEs) and 4% reported a serious AE; nasopharyngitis (17%), upper respiratory tract infection (12%), worsening of axSpA (9%), headache (8%), and diarrhoea (6%) were the most common. During period 2, incidence of AEs was similar for ADA and PBO (65% vs 69%), incidence of serious AEs was higher for PBO vs ADA (7% vs 1%), and the most common AEs in both the ADA and PBO groups were nasopharyngitis (16% vs 13%), upper respiratory tract infection (13% vs 8%), and worsening of axSpA (6% vs 14%; none serious). Conclusions: In pts with nr-axSpA who achieved sustained remission with ADA, continued therapy was associated with significantly more pts maintaining remission and lower disease activity than treatment withdrawal. These results support the continuation of ADA therapy after achievement of sustained remission. Safety findings were consistent with established safety profile of ADA. Acknowledgements: AbbVie funded, contributed to design, data collection, analysis and interpretation of the data of the study, and in writing, review, approval of the publication. Medical writing:Maria Hovenden, PhD; Janet E. Matsuura, PhD, of CPS; funded by AbbVie. Disclosure of Interest: R. Landewé Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB, and Wyeth, Consultant for: Abbott/AbbVie, Ablynx, Amgen, AstraZeneca, Bristol-Myers Squibb, Celgene, Janssen (formerly Centocor), Galapagos, GlaxoSmithKline, Novartis, Novo Nordisk, Merck, Pfizer, Roche, Schering-Plough, TiGenix, UCB, and Wyeth, Speakers bureau: Abbott/AbbVie, Amgen, Bristol Myers Squibb, Janssen (formerly Centocor), Merck, Pfizer, Roche, Schering-Plough, UCB, and Wyeth., J. Sieper Consultant for: AbbVie, Janssen, Lilly, Merck, Novartis, Pfizer, Sun Pharma, and UCB, Speakers bureau: AbbVie, Janssen, Lilly, Merck, Novartis, and Pfizer, P. Mease Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun Pharma, and UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Janssen, Lilly, Novartis, Pfizer, Sun Pharma, and UCB, Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Genentech, Janssen, Novartis, Pfizer, and UCB, R. Inman Consultant for: AbbVie, Amgen, Janssen, Lilly, Merck, and Novartis, X. Wang Shareholder of: AbbVie, Employee of: AbbVie, M. Li Shareholder of: AbbVie, Employee of: AbbVie, A. Pangan Shareholder of: AbbVie, Employee of: AbbVie, J. Anderson Shareholder of: AbbVie, Employee of: AbbVie